Oil palm empty fruit bunch-polyurethane composite: the effect of PU-EFB mixture on strength characteristics / Adnan Derahman … [et al.] - Derahman, Adnan; Mohd Latib, Farah Wahida; Muhamad, Noor Safwan; Ab. Latif, Amminudin (2015)
Currently, the race for creating biodegradable items has expanded immensely. Distinctive methodologies have been endeavored to utilize biomass as common biopolymer. Accessible arrangement is to join the petroleum and bio-assets (plant and horticulture stock) to create a helpful item having the imperative expense execution properties for genuine applications. There are many methods that have been applied to improve the behavior of the soil and increase the strength and characteristics of the soil. In this research, polyurethane (PU) foam/resin was utilized and consolidated with oil palm empty fruit bunch (EFB) as fiber from palm oil. PU foam are normally utilized as a part of numerous applications including bundling, padding, space filling and protection yet all the more frequently in geotechnical designing while oil palm EFB is a unique reinforcing material as it is non-hazardous, renewable, and readily available at relatively low cost due to established technology to extract the fibers compared to other commercially available fibers. Different ratio of PU and EFB was used to optimize the composition in order to increase the ultimate strength of the composition. Shear strength of these two combinations were measured by conducting the specific test which was Unconfined Compression Test (UCT). This test measured the undrained strength and stress-strain characteristic of these mixtures. From the analysis, it was found that fiber changed the failure mode of PU foam into a more ductile behavior. Having a 25 % of fiber can double the strength of the foam, but increasing the fiber further reduces the strength.